2018
DOI: 10.1038/s41598-018-29874-w
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 signaling stimulates miR-21 expression in bovine cumulus cells during in vitro oocyte maturation

Abstract: MicroRNAs are potent regulators of gene expression that have been widely implicated in reproduction and embryo development. Recent studies have demonstrated that miR-21, a microRNA extensively studied in the context of disease, is important in multiple facets of reproductive biology including folliculogenesis, ovulation, oocyte maturation and early mammalian development. Surprisingly, little is known about the mechanisms that regulate miR-21 and no studies have characterized these regulatory pathways in cumulu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 92 publications
(104 reference statements)
1
25
0
1
Order By: Relevance
“…Activation of p-STAT3 was found to be involved in meiotic spindle assembly and chromosome segregation in mouse oocytes ( 23 ), and STAT3 activation was able to stimulate the progression of meiosis ( 24 ). In vitro maturation of COCs supplemented with STAT3 inhibitor stattic was found to block cumulus expansion ( 25 ). Based on these findings, we speculated that the inhibition of EGFR and MAPK1/3 in the ovary had been negated by the upregulation of STAT3, thus no effects of lapatinib treatment were noted on ovarian reserve or fertility potential in vivo ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of p-STAT3 was found to be involved in meiotic spindle assembly and chromosome segregation in mouse oocytes ( 23 ), and STAT3 activation was able to stimulate the progression of meiosis ( 24 ). In vitro maturation of COCs supplemented with STAT3 inhibitor stattic was found to block cumulus expansion ( 25 ). Based on these findings, we speculated that the inhibition of EGFR and MAPK1/3 in the ovary had been negated by the upregulation of STAT3, thus no effects of lapatinib treatment were noted on ovarian reserve or fertility potential in vivo ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Results revealed that COCs treated with LIF showed higher expression of miR-21 in both cumulus cells and oocytes when compared to immature oocytes. Increased expression of miR-21 has previously been described in COCs after 24 h in culture under serum free conditions, without supplements or in culture supplemented with LIF alone 12 and miR-21 is recognized as a highly abundant miRNA in cumulus cells 9,38 that is present throughout folliculogenesis 38 . In www.nature.com/scientificreports/ addition, miR-21 is implicated in apoptosis, cell cycle arrest, tumor suppression and chromosome alignment 36 .…”
Section: Discussionmentioning
confidence: 89%
“…Recent studies have shown that miRNA levels change during oocyte maturation and ovarian follicular development implying a regulatory role 9,10 . miRNAs including miR-21 11,12 , miR-155 9,13 and miR-34c are expressed or consistently change their expression patterns from the GV oocyte to the 2-cell embryo stage 14 . miR-146a is a potent regulator of the immune response and inflammation 15 .…”
mentioning
confidence: 99%
“…Details regarding the mechanism through which STAT3 reduced miR-30a-5p expression are warranted; nonetheless, this study showed that the downregulation of miR-30a-5p played a role in anti-apoptosis. STAT3 has been reported to both induce and repress microRNA expression [ 21 , 22 , 23 , 24 ]. One of the possible mechanisms might be the interaction of STAT3 with G9a and the epigenetic suppression of gene expression through methylation of H3K9, which thereby downregulate the expression levels of miR-200c and miR-145 [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%